Effects of a personalized PERMA-based intervention on the mental health of junior high school students: a randomized clinical trial - Zhang, Lei; Chen, Xiao; Wan, Hengjing (Frontiers in Psychology, 2025)
BackgroundAdolescence is a critical period marked by increasing academic pressure and evolving self-cognition, making junior high school students particularly vulnerable to mental health challenges. Positive psychology interventions (PPIs) based on the PERMA framework have shown promise in improving well-being, but studies targeting Chinese middle school students remain limited. This study aimed to evaluate the effectiveness of a personalized PERMA-based PPI in enhancing well-being and resilience among junior high school students in Shanghai, China.MethodsA total of 154 students were randomly assigned to either an experimental group (n = 77) or a control group (n = 77). The experimental group participated in an eight-week intervention involving weekly sessions designed to enhance the five dimensions of the PERMA framework: Positive Emotion, Engagement, Relationships, Meaning, and Accomplishment. The control group continued with regular psychology courses. Pre- and post-intervention assessments were conducted using validated scales measuring well-being, resilience, and coping styles. Paired t-tests were used for within-group comparisons and ANCOVA for between-group comparisons, analyzed in R (v4.2.2).ResultsAt baseline, the experimental group had lower scores in positive emotion (12.4 ± 4.02 vs. 13.8 ± 4.39), relationships (12.4 ± 4.22 vs. 13.8 ± 4.05), and total well-being (47.5 ± 13.6 vs. 51.1 ± 14.4) compared to the control group. After the intervention, the experimental group showed significant improvements in positive emotion (+2.3), relationship (+2.2), and total well-being (+3.4). The experimental group also demonstrated significant increases in accomplishment (+1.4), engagement (+1.2), goal focus (+2.1), positive cognition (+1.5), and total resilience (+5.2). No significant changes were observed in coping styles, though slight improvements in positive coping tendency (from −0.02 to −0.13) and a slight decrease in negative coping tendency (from −0.02 to −0.01).ConclusionThis study provides empirical evidence for the effectiveness of personalized PPIs in addressing adolescents’ mental health challenges, with notable improvements in well-being and resilience. Limitations include the small sample size for paired analysis (n = 58) and the timing of the intervention during the final exam period, which might have introduced biases. Future research should explore the sustained effects of such interventions and their scalability across diverse educational settings.